Two different unilateral percutaneous vertebroplasty approaches for acute osteoporotic vertebral compression fractures: clinical and radiological outcomes - Anquan Huang; Haijun Liu; Yubo Liu; Jun Shen; Guoqing Zhu; Yefeng Wang; Shiming Li; Tianming Zou; Chenxi Gu; Bin Lv (BMC Musculoskeletal Disorders)
Abstract Objective To investigate whether the unilateral posterosuperior approach PVP is superior to the traditional unilateral transpedicular approach in the treatment of acute osteoporotic vertebral compression fractures (OVCFs). Methods A retrospective study was conducted on 167 patients with single-segment acute OVCFs admitted to our hospital from September 2019 to March 2022. Patients were divided into two groups according to the type of intraoperative approach used: the unipedicular posterosuperior approach vertebroplasty (UPV) group (n = 85) and the unilateral transpedicular approach vertebroplasty (UTV) group (n = 82). Surgical data, including operation time, blood loss, fluoroscopy frequency, puncture needle crossing the midline during surgery, and bone cement injection volume, were collected. Imaging data, such as vertebral height, distribution of bone cement, and cement leakage, were analyzed. Clinical efficacy indicators, including the Visual analogue scale (VAS) score and Oswestry Disability Index (ODI), were compared. Additionally, the occurrence of vertebral refracture, adjacent vertebral fracture, and postoperative complications were assessed. Results Both groups were followed up for an average of 13.6 months (range: 12–24 months). No statistically significant differences were detected between the UPV and UTV groups in terms of the VAS and ODI scores or the vertebral height. The two groups had similar blood loss rates, fluoroscopy frequencies, and operation times. However, the UPV group presented a greater volume of bone cement injected and a better dispersion pattern of bone cement (10.75 ± 0.48 vs. 7.56 ± 1.86) (P < 0.05). The occurrence of vertebral collapse after surgery was positively correlated with the distribution of bone cement. Cement leakage was observed in 5 patients in the UPV group and 10 patients in the UTV group. The UPV group had 2 cases of adjacent vertebral refracture within six months, whereas the UTV group had 5 cases. One adverse event, pneumothorax, occurred in the UPV group. However, due to the retrospective nature of the study, there was a lack of control over confounding variables such as age, bone mineral density, and comorbidities, which may affect the interpretation of the results. Conclusions PVP via the unilateral approach effectively relieves back pain in patients with OVCFs. The unilateral posterosuperior approach allows for the injection of a greater volume of bone cement, resulting in a more even distribution within the vertebral body. However, caution should be exercised to avoid excessive lateral puncture points.